2020
DOI: 10.1093/ajh/hpaa066
|View full text |Cite
|
Sign up to set email alerts
|

Icotinib Attenuates Monocrotaline-Induced Pulmonary Hypertension by Preventing Pulmonary Arterial Smooth Muscle Cell Dysfunction

Abstract: Background Aberrant activation of epidermal growth factor receptor (EGFR) signaling pathway is associated with the pathogenesis of pulmonary hypertension (PH). However, the effect of icotinib, a first generation of EGFR tyrosine kinase inhibitor (EGFR-TKI), on PH remains to be elucidated. Methods PH rat model was established by a single intraperitoneal injection of monocrotaline (MCT, 60 mg/kg). Icotinib (15, 30, and 60 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…To some extent, the biological patterns involved in PAH share several features with cancer, including unrestrained cell proliferation, enhanced migration, and resistance to apoptosis [ 40 ]. High proliferation and migration of PASMCs have been associated with the PI3K/AKT and ERK signaling pathways [ 41 45 ]. PI3K is a cytoplasmic lipid kinase involved in the regulation of a variety of processes that are critical for cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, the biological patterns involved in PAH share several features with cancer, including unrestrained cell proliferation, enhanced migration, and resistance to apoptosis [ 40 ]. High proliferation and migration of PASMCs have been associated with the PI3K/AKT and ERK signaling pathways [ 41 45 ]. PI3K is a cytoplasmic lipid kinase involved in the regulation of a variety of processes that are critical for cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The reactions were visualized using diaminobenzidine chromogenic solution. The degree of muscularization was defined by the proportion of α -SMA-positive parts of circumference according to a previous study [ 19 ]. The muscularization of distal vessels with diameter 25–100 μ m was quantified, and the percentages of nonmuscularized, partially muscularized, and fully muscularized vessels were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that Peng et al. ( 23 ) reported that icotinib can significantly reduce the right ventricular systolic blood pressure and right ventricular hypertrophy index of cytroline-induced pulmonary hypertension in rats, and improve the pulmonary vascular remodeling induced by monocrotaline, and proposed that this effect may prevent the dysfunction of pulmonary artery smooth muscle cells by inhibiting the EGFR-Akt/ERK signaling pathway.…”
Section: Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitorsmentioning
confidence: 99%